Development of Science E-Modules for Middle Schools Integrated with Al-Qur’an Verses with Virtual Simulation of Solar System Material - Wulandari, Aisyah Sri; Permana, Niki Dian; Susilawati, Susilawati; Syarif, Muhammad Ilham; Ilhami, Aldeva (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
This research was conducted to produce a science e-modules for middle schools integrated with the Al-Qur’an versed, assisted by virtual simulations on solar system material. These teaching materials were made to support students learning independently with engaging content in which they were equipped with virtual simulations. The author conducted the research using research and development methods by adapting Borg and Gall’s research design. The step in this research was limited by the fifth step, namely the main primary product revision. This was due to the authors’ conditions in the development process. The results of the validity of the science e-module product have been declared valid based on the results of validation by Al-Qur’an verses integration experts, learning materials experts, and teaching materials experts, with the category of all assessments being very good or feasible to use. In addition, the science e-module for middle school integrated verses of the Al-Qur’an assisted virtual simulation on the stated practical to use for students in learning. The student responses related to the science e-module product for middle school integrated verses Al-Qur’an assisted virtual simulation on very positive.